2016
DOI: 10.1097/md.0000000000003544
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Radial Shock Wave Therapy on Spasticity of the Upper Limb in Patients With Chronic Stroke

Abstract: Recently, studies have reported that extracorporeal shock wave therapy (ESWT) is a safe, noninvasive, alternative treatment for spasticity. However, the effect of ESWT on spasticity cannot be determined, because most studies to date have enrolled small patient numbers and have lacked placebo-controlled groups and/or long-term follow-up. In addition, whether varying the number of ESWT sessions would affect the duration of the therapeutic effect has not been investigated in a single study. Hence, we performed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
122
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(135 citation statements)
references
References 34 publications
4
122
0
9
Order By: Relevance
“…The results of present study were in agreement with previous studies that showed that radial SWT has a positive effect on spasticity in patients with stroke and cerebral palsy [11,[20][21][22]29]. Standard guidelines for the use of SWT on soft tissue have not been established.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The results of present study were in agreement with previous studies that showed that radial SWT has a positive effect on spasticity in patients with stroke and cerebral palsy [11,[20][21][22]29]. Standard guidelines for the use of SWT on soft tissue have not been established.…”
Section: Discussionsupporting
confidence: 83%
“…Standard guidelines for the use of SWT on soft tissue have not been established. However repeated sessions of radial SWT result in a more noticeable and longer-lasting effect [22]. Radial SWT is characterized by having a larger therapeutic area compared with focused SWT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their research, Keng et al revealed that 3 months post stroke, spasticity occurred in 33% of the patients [6]. The level of spasticity is usually assessed with Modified Ashworth Scale (MAS) and Modified Tardieu Scale (MTS) [7][8][9][10][11][12][13][14][15]. …”
mentioning
confidence: 99%